2015
DOI: 10.1063/1.4931623
|View full text |Cite
|
Sign up to set email alerts
|

Three-terminal stand-alone superconducting terahertz emitter

Abstract: We report on the electrothermal behavior and the terahertz emission properties of a stand-alone Bi2Sr2CaCu2O8 intrinsic Josephson junction stack contacted in a three-terminal configuration. One terminal is used as a collective ground while the other two, contacting the stack from its right and left side, allow to vary the current injection profile. At high bias, a hot spot forms in the stack. Its appearance and position can be controlled by varying the ratios of the injected currents. Depending on this ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 51 publications
0
31
1
Order By: Relevance
“…For B x = 0 the emission is strong for I between 10 and 20 mA and T bath between 10 and 40 K. One notes short period oscillations in P e which presumably are extrinsic in origin. These oscillations have been observed before 28,35,66 . Apart from that the plots clearly show that, for B x = 5.9 mT, over a wide range of currents and bath temperatures P e has increased significantly, in some of the stripe-like regions up to a factor of 2.7.…”
Section: Comparison To Experimentsmentioning
confidence: 82%
See 1 more Smart Citation
“…For B x = 0 the emission is strong for I between 10 and 20 mA and T bath between 10 and 40 K. One notes short period oscillations in P e which presumably are extrinsic in origin. These oscillations have been observed before 28,35,66 . Apart from that the plots clearly show that, for B x = 5.9 mT, over a wide range of currents and bath temperatures P e has increased significantly, in some of the stripe-like regions up to a factor of 2.7.…”
Section: Comparison To Experimentsmentioning
confidence: 82%
“…Other properties such as the emission frequency seem to be basically independent of the hot spot position, leading to some debate as to whether the hot spot is helpful for radiation or just coexists with the radiating regions 20,22,23 . In fact, recent results showed that there is a strong interaction 28 . Further, cooling has been improved by sandwiching the stacks between substrates with high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The stack geometry is sketched in figure 1. The sample preparation is similar to the one described in [26]. First, the crystal is glued with epoxy onto a Si substrate.…”
Section: Samples and Measurementsmentioning
confidence: 99%
“…The local temperature distributions TðrÞ of the IJJ mesa devices have been measured in detail, and the results have been discussed in comparison with theoretical studies. [14][15][16][40][41][42][43][44][45]51,[63][64][65][66][78][79][80] These studies concluded that the spontaneous formation of a local temperature instability known as a hot spot can occur in the IJJ-THz emitter device due to both the quasi-two-dimensional thermal and electrical conductivities, the latter yielding a semiconducting-like temperature dependence of the c-axis normal state resistivity for under-doped Bi2212 single crystals. Previous studies revealed that a hot spot, within which the local temperature TðrÞ > T c , acts as a shunt resistance inserted parallel to the 0021-8979/2018/124(3)/033901/9/$30.00…”
Section: Introductionmentioning
confidence: 96%